Private Lecturer Income Analysis - asnah, Asnahwati (Adpebi Science Series, 2022)
There are many cases where the income of private lecturers is much lower than the income of public lecturers, even though the government already regulates it in the Law on Teachers and Lecturers. Departing from this phenomenon, the authors are interested in conducting research on the income of private lecturers. This study aims to evaluate and recommend a model for increasing the income of private lecturers. This research was conducted with a descriptive approach. Data collection techniques in this study used observation techniques and survey techniques by distributing questionnaires to private lecturers who were used as respondents. The results of this study stated that of the nine sources of income for the lecturers studied, it was found that eight items of income sources were in the poor category and only one item was in the good category, namely serdos allowance. In other words, the increase in the income of private lecturers is mostly dominated by serdos allowances. To further increase the income of private lecturers, it is hoped that the campus or institution will provide support to lecturers in obtaining income from other sources, such as compiling textbooks and obtaining research and service grants from DIKTI.